PSYCHIATRIC MORBIDITY IN PATIENTS WITH CHRONIC KIDNEY - Ramasubramanian, Vikhram (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Background Chronic Kidney Disease (CKD) is a public health problem that tends to take dimensions of epidemic and has serious impact on quality of patient's life. Aim The aim of the present study was to evaluate the psychiatric morbidity in chronic kidney disease patients undergoing haemodialysis. Materials and Methods This study enrolled 130 chronic kidney disease patients undergoing haemodialysis. Psychological characteristics of the patients were assessed with the Mini-International Neuropsychiatric Interview (MINI). Results The mean age of patients undergoing haemodialysis were 53years ± 13.9 and the mean age of male were 52.79 yrs± 13.9 and female were 53.37yrs ± 12.8.9.The results of renal dysfunction showed mean 2.99 yrs± 3.12, with mean duration of male is 3.23 ± 3.5 yrs and female is 2.57yrs ± 2.2.40% of patients (n=52) were diagnosed with psychiatric illness, 27.69% male patients (n=36),12.3% female patients(n=16).The duration of renal disease (mean=2.99yrs) was compared with duration of psychiatric illness (mean=1.34yrs). It was observed that difference between the means is statistically significant (p = 0.02).The results showed that the mean duration of mental illness was 1.34yrs + 1.47. 69.2% were males (n=36), and 16, 30.8% were females. Most of the patients (n=25, 19.23%) diagnosed to have a psychiatric illness belonged to the age group of 40-60 yrs. The age of onset of renal disease in our sample was 50yrs+ 14.05 and the age of onset of psychiatric morbidity was 50.92 yrs+13.63. Conclusion The present study has been helpful in understanding the onset of psychiatric illness among the CKD patients undergoing haemodialysis. Keywords Psychiatric Morbidity, Dialysis, Chronic renal failure, Psychological factors